Luigi Nono: Zur Frage der Wende - Tadday, Ulrich (Munich Edition text + kritik, 2024)
The compositional style of Luigi Nono (1924-1990) changed from the mid-1970s onwards. From then on, it was less the political message and more the sonic exploration, to use Paulo de Assis' words, that seemed to be in the composer's interest.But does this change, which characterizes Nono's late work, really come into its own with the term “turn”, which has become commonplace, to describe the relationship between the political and the aesthetic-musical in the late Nono in a differentiated way? On the occasion of Luigi Nono's 100th birthday, the authors of this volume explore this highly complex question using various works - from “..... sofferte onde serene ...” for piano and tape (1975/76) to “Prometeo. Tragedia dell'ascolto” (1984) and far beyond. (Translated with DeepL.com)With contributions by Paulo de Assis, Pauline Driesen, Laurent Feneyrou, Jörn Peter Hiekel, Julia Kursell and Matteo Nanni.
Keywords: Nono, Luigi -- 1924-1990